THE CHARACTERS AND OBSTACLES OF ISLAMIC MODERATION PRACTICE - Ahmad Bustomi (MODERATIO: Jurnal Moderasi Beragama, 2022)
Abstract: This article can give explanation about Islamic moderation values as good way to make Indonesia which has the biggest Islam Follower in the world becomes trend setter of the world. This article come due to the danger of radicalism which stronger in 212 movement. For more specific it will be more docuse onto character and the obstacle in practice. This research is library research and Data collected method uses deskriptiv-interpretation. Data consist of primer data and secondary data. The result of this research show first, Character of Islamic Moderation consist of six character: Base on divinity (Rububiyah), Base on prophetic guidance, Compatible with human fitrah, Without conflict, Consistent, Universal and comprehensive. Second, Obstacles of moderation practice (Islam Washatiyyah) consist of Foolishness, Fanaticism of faction (Ta’asub) snd Exaggeration. Keyword: Moderation Practice, moderate character, religious moderation obstacle. Abstrak: Artikel ni memberikan penjelasan tentang nilai-nilai moderasi Islam sebagai jalan terbaik untuk membuat Indonesia yang memiliki pemeluk agama Islam terbesar di dunia menjadi pusat perhatian dunia. Tulisan ini hadir dikarenakan bahaya radikalisme yang semakin menguat pasca Gerakan demonstrasi 212. Lebih spesifik lagi akan menjadi lebih difokuskan terhadap karakteristik moderasi islam dan hambatan-hambatan moderasi Islam dalam praksisnya. Penelitian ini adalah penelitian kepustakaan dan metode pengumpulan datanya adalah interpretasi deskriptif. Data terdiri dari data primer dan data sekunder. Hasil penelitian menunjukkan bahwa pertama, Karakter moderasi islam terdiri dari enam karakter, yaitu Berasaskan Ketuhanan (Rububiyah), Berlandaskan petunjuk kenabian, kompatibel dengan fitrah manusia, terhindar dari pertentangan, konsisten, bermuatan universal dan komprehensip. Kedua, hambatan dari praktik moderasi (Islam Washatiyyah) adalahKebodohan, fanatisme golongan, sikap berlebih-lebihan.